Lembaga Keuangan Mikro Adat Sebagai Penggerak Perekonomian Desa Lambing - Putu Krisna Adwitya Sanjaya; Made Heny Urmila Dewi (UNHI Press, 2020)
This study aims to analyze the performance of Lambing Badung Regency customary microfinance institutions which are assessed from four perspectives, namely: (1) financial perspective, (2) customer perspective, (3) internal business process perspective, and (4) learning and growth perspective. This study is a type of quantitative descriptive study that explains the performance of customary microfinance institutions in 2017 - 2019. Data are collected using questionnaires, documentation, and interviews which are then analyzed using the balanced scorecard approach. This study found the fact that the performance of Lambing indigenous microfinance institutions based on four perspectives: (1) the overall finance is in the healthy category, (2) the overall customer is in a good category, (3) the internal business process is classified as efficient, and (4) learning and growth as a whole are in a good category. By having a good performance, this institution is expected to be more developed and of course, with the development of customary microfinance institutions, the economy in the area will also be increasingly stretched which can become a pillar driving the economy so that there is an acceleration of the welfare of rural communities.